Nanoemulsion Composed of α-Tocopherol Succinate and Dequalinium Shows Mitochondria-Targeting and Anticancer Effects - Le Thi Thuy; Seulgi Lee; Viet Dongquoc; Joon Sig Choi (MDPI AG, 2023)
Targeted drugs have been used to treat mitochondrial dysfunction-related diseases, including metabolic disorders and cancer; however, targeting and penetrating intracellular organelles remains a challenge. Dominant targeting approaches for therapeutic delivery are detailed in many nanoemulsion studies and show the tremendous potential of targeted delivery to inhibit cancer cell growth. Dequalinium (DQA) and α-tocopherol succinate (α-TOS) are good agents for targeting mitochondria. In this study, we aimed to develop a mitochondria-targeting emulsion, using DQA and α-TOS (DTOS), for cancer treatment. DTOS emulsions of 150-170 nm in diameter were formulated using homogenization. DQA and α-TOS were used as bifunctional agents (surfactants) to stabilize the nanoemulsion and anticancer drugs. Various molar ratios of DQA and α-TOS were tested to determine the optimal condition, and DTOS 5-5 was selected for further study. The DTOS emulsion showed improved stability, as evidenced by its ability to remain stable for three years at room temperature. This stability, combined with its effective targeting of mitochondria, led to inhibition of 71.5% of HeLa cells after 24 h. The DTOS emulsion effectively inhibited spheroid growth in the 3D model, as well as prevented the growth of HeLa cells grafted onto zebrafish larvae. These results highlight the DTOS emulsion's promising potential for mitochondria-targeting and cancer treatment.